Anterior Apical Cores In The Initial Prostate Biopsy Does Not Increase Detection Of Significant Prostate Cancer - Ekin, Rahmi Gokhan; Zorlu, Ferruh; Akarken, Ilker; Yildirim Ekin, Zubeyde; Tarhan, Huseyin; Koc, Gokhan; Kucuk, Ulku; Bayol, Umit (Urology Journal, 2015)
<!–[if gte mso 9]> <![endif]–> Purpose To examine the effect of routine sampling anterior apical cores in the initial prostate biopsy among patients that 14-cores of prostate biopsy planned. Methods Five-hundred twenty-eight patients with increased prostate-specific antigen levels and/or abnormal digital rectal examination underwent transrectal ultrasound and initial prostate biopsy between November 2012 and October 2013. We performed routinely 12-cores extended prostate biopsy plus 2 anterior apex samples that were taken from the junction of urethra and apex. Site-specific and unique cancer detection rate, tumor characteristics and biopsy related pain were evaluated. Results Prostate cancer was detected in 147 of 451 patients (32.6%). Lateral base of the prostate had the highest importance for cancer detection with 128 of 451 patients (28.3%) and unique cancer detection with 17 of 40 patients (43.5%). Anterior apex (n=6) was in third place after the lateral apex (n=8). The patients diagnosed by anterior apex cores were all clinically insignificant prostate cancer. The cancer diagnosis rate would be 31% if 12-cores biopsy was used, but that rate found 32.6% in 14-cores biopsy (p=0. 016). Average biopsy pain, right anterior apex biopsy pain and left anterior apex biopsy pain were found 0.61, 1.06 and 1.08, respectively. When right and left anterior apex biopsy pain is compared to average biopsy pain, the pain level was found that statistically significant higher in the biopsies of right and left anterior apex (p=0.040 and p=0.042). Conclusions According to our results, although more prostate cancer diagnosis would be done with 14-cores prostate biopsy, it should not be forgotten that those patients might have clinically insignificant prostate cancer.